Synthesis, Characterization and Luminescent Properties of Bipodal and Tripodal Pyrazole and Triazole Lanthanide Coordination Complexes - Tofah , K.P. (University of Ghana, 2019)
Lanthanide complexes have been established as promising agents in their application as catalysts and photo-luminescent materials. Recent research has been geared towards the optical application of these lanthanide complexes, especially as organic light-emitting diodes (OLED) for TV screens, phones and other portable electronic devices. The luminescent ability of these complexes is largely dependent on the choice of ligand environment. We report here for the first time lanthanide complexes bearing three classes of ligands, mainly a heteroscorpionate (N^N^O) ligand of the form Pz2R(CHPhOH) (Figure 1.0-A), (N^N) 1-(2-Picolyl)-4-phenyl-1H- 1,2,3-triazole (Figure 1.0-B) and (N^N) 3,6-(dipyridyl)-1,2,4,5-tetrazine (Figure 1.0-C). The coordination complex of the lanthanum salts (Pr, Dy, Gd and Tb), have been synthesized and characterized by 1H-NMR, 13C-NMR and FT-IR. The electronic and luminescence property of the ligands and complexes have been studied using Cyclic Voltammetry, UV-vis and spectro-fluorophotometric studies.
MPhil. Chemistry
Keywords: Bipodal; Tripodal; Pyrazole; Triazole Lanthanide